PENGARUH KONSENTRASI KATALIS DAN KECEPATAN PENGADUKAN PADA SINTESIS BIODIESEL MINYAK KELAPA SAWIT DENGAN KO-PELARUT METIL ESTER - Daryono, Elvianto Dwi; Dewi, Rini Kartika; Anggorowati, Dwi Ana (Indonesian Journal of Pure and Applied Chemistry, 2026)
The transesterification process is hindered by the many processing steps required, and the results are often suboptimal. The interesterification process using a methyl ester co-solvent offers a solution to this issue. The methyl ester co-solvent accelerates the reaction and eliminates the need for a separation stage at the end of the process. This study aims to determine the effects of catalyst concentration and stirring speed on methyl ester yield in the interesterification of palm oil to biodiesel using a methyl ester co-solvent. A total of 250 g of oil was used, with an oil-to-methyl acetate molar ratio of 1:6. The reaction was carried out at 60 °C, using 15% co-solvent, a reaction time of 1 hour, KOH catalyst concentrations ranging from 0.25% to 1%, and stirring speeds between 600 and 1,000 rpm. The oil, methyl acetate, and catalyst were placed into a three-neck flask, and the reaction was conducted according to the specified operating conditions. Optimum conditions for palm oil interesterification were achieved with a KOH catalyst concentration of 0.5% and a stirring speed of 800 rpm, resulting in a crude yield of 93.1%, a methyl ester concentration of 43,654 mg/L, and an acid value of 0.42 mg KOH/g, meeting the requirements of SNI 7182:2015.